The role of psychological safety and psychological capital in linking leadership curiosity to employee creative performance - Barbara Rebecca Mutonyi; Renate Fredheim; Terje Slåtten (Cogent Social Sciences)
This study examines the relationships between the leadership display of curiosity, employees’ creative performance, and two psychological conditions mediating this relationship. The two psychological conditions are represented by (i) psychological capital and (ii) psychological safety. A sample of 181 employees from different hospitality organizations participated in this study. The sample was analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM) with the SmartPLS 4 statistical program. Leadership display of curiosity are directly related to employees’ creative performance. Employees’ psychological capital mediates the relationship between leadership and creative performance. Psychological safety was affected by the leadership’s display of curiosity but did not mediate the relationship between the leadership’s display of curiosity and creative performance. Leadership display of curiosity, psychological capital, and psychological safety explain almost 50 percent (48,2%) of employees’ creative performance variance. Overall, the findings reveal that leadership display of curiosity have a substantial impact on both employees’ creative performance and psychological capital, as well as the psychological safety climate in the organization. Accordingly, an essential implication of this study is to develop the level of curiosity among leaders and consider it a resource that organizations can capitalize on. This study contributes to a relatively new research domain, focusing on and revealing the role of the leadership display of curiosity within organizations.